Autophagy Enhances Bacterial Clearance during P. aeruginosa Lung Infection - Junkins, Robert D. (Public Library of Science, 2013)
Pseudomonas aeruginosa is an opportunistic bacterial pathogen which is the leading cause of morbidity and mortality among cystic fibrosis patients. Although P. aeruginosa is primarily considered an extacellular pathogen, recent reports have demonstrated that throughout the course of infection the bacterium acquires the ability to enter and reside within host cells. Normally intracellular pathogens are cleared through a process called autophagy which sequesters and degrades portions of the cytosol, including invading bacteria. However the role of autophagy in host defense against P. aeruginosa in vivo remains unknown. Understanding the role of autophagy during P. aeruginosa infection is of particular importance as mutations leading to cystic fibrosis have recently been shown to cause a blockade in the autophagy pathway, which could increase susceptibility to infection. Here we demonstrate that P. aeruginosa induces autophagy in mast cells, which have been recognized as sentinels in the host defense against bacterial infection. We further demonstrate that inhibition of autophagy through pharmacological means or protein knockdown inhibits clearance of intracellular P. aeruginosa in vitro, while pharmacologic induction of autophagy significantly increased bacterial clearance. Finally we find that pharmacological manipulation of autophagy in vivo effectively regulates bacterial clearance of P. aeruginosa from the lung. Together our results demonstrate that autophagy is required for an effective immune response against P. aeruginosa infection in vivo, and suggest that pharmacological interventions targeting the autophagy pathway could have considerable therapeutic potential in the treatment of P. aeruginosa lung infection.